2017
DOI: 10.1063/1.5004124
|View full text |Cite
|
Sign up to set email alerts
|

Influential factors on thermoacoustic efficiency of multilayered graphene film loudspeakers for optimal design

Abstract: Graphene thermoacoustic loudspeakers, composed of a graphene film on a substrate, generate sound with heat. Improving thermoacoustic efficiency of graphene speakers is a goal for optimal design. In this work, we first modified the existing TA model with respect to small thermal wavelengths, and then built an acoustic platform for model validation. Additionally, sensitivity analyses for influential factors on thermoacoustic efficiency were performed, including the thickness of multilayered graphene films, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Regarding thin metal film heaters and underlying thermal insulators, many studies have been conducted by using varied combinations: suspended Al wires-air (Niskanen et al, 2009), Si nanowires-polymer or -glass (Tian et al, 2011a), indium-tin-oxide film-glass (Daschewski et al, 2015), Si nanoparticles-sapphire (Odagawa et al, 2010), conducting polymers-glass (Tian et al, 2011b), thin Au film-porous polymer (Chitnis et al, 2012), thin Ag–Pd film-glass-Al 2 O 3 (Nishioka et al, 2015), carbon nanotube (CNT)-air (Xiao et al, 2011), or -grooved Si (Wei et al, 2013), graphene-polymer (Suk et al, 2012; Tian et al, 2014; Kim et al, 2016; Tao et al, 2016; Sbrockey et al, 2018), -porous Al 2 O 3 (Tian et al, 2012), or -glass (Fei et al, 2015), CNT-laser-scribed graphene-polymer (Yeklangi et al, 2018), and W-Al 2 O 3 -polymer (Brown et al, 2016). The basic characteristics of these devices are consistent with the theoretical analyses of the thermo-acoustic effect and its key factors (Hu et al, 2010, 2012a,b, 2014; Vesterinen et al, 2010; Daschewski et al, 2013; Lim et al, 2013; Yang and Liu, 2013; Wang et al, 2015; Tong et al, 2017; Xing et al, 2017). Making use of the non-resonant and broad-band emissivity with no harmonic distortions, possible applications have been pursued to audible compact speaker under a full digital drive, probing source for 3-dimentional object sensing in air, acoustic pressure generator for noncontact actuation, directivity control under phased array configuration, loud speaker, noise cancellation, thermoacoustic tomography, and thermoacoustic sound projector (Koshida, 2017c; Aliev et al, 2018; Bobinger et al, 2018; Julius et al, 2018; Liu et al, 2018; Song et al, 2018).…”
Section: Emissive Properties and Applicationssupporting
confidence: 81%
“…Regarding thin metal film heaters and underlying thermal insulators, many studies have been conducted by using varied combinations: suspended Al wires-air (Niskanen et al, 2009), Si nanowires-polymer or -glass (Tian et al, 2011a), indium-tin-oxide film-glass (Daschewski et al, 2015), Si nanoparticles-sapphire (Odagawa et al, 2010), conducting polymers-glass (Tian et al, 2011b), thin Au film-porous polymer (Chitnis et al, 2012), thin Ag–Pd film-glass-Al 2 O 3 (Nishioka et al, 2015), carbon nanotube (CNT)-air (Xiao et al, 2011), or -grooved Si (Wei et al, 2013), graphene-polymer (Suk et al, 2012; Tian et al, 2014; Kim et al, 2016; Tao et al, 2016; Sbrockey et al, 2018), -porous Al 2 O 3 (Tian et al, 2012), or -glass (Fei et al, 2015), CNT-laser-scribed graphene-polymer (Yeklangi et al, 2018), and W-Al 2 O 3 -polymer (Brown et al, 2016). The basic characteristics of these devices are consistent with the theoretical analyses of the thermo-acoustic effect and its key factors (Hu et al, 2010, 2012a,b, 2014; Vesterinen et al, 2010; Daschewski et al, 2013; Lim et al, 2013; Yang and Liu, 2013; Wang et al, 2015; Tong et al, 2017; Xing et al, 2017). Making use of the non-resonant and broad-band emissivity with no harmonic distortions, possible applications have been pursued to audible compact speaker under a full digital drive, probing source for 3-dimentional object sensing in air, acoustic pressure generator for noncontact actuation, directivity control under phased array configuration, loud speaker, noise cancellation, thermoacoustic tomography, and thermoacoustic sound projector (Koshida, 2017c; Aliev et al, 2018; Bobinger et al, 2018; Julius et al, 2018; Liu et al, 2018; Song et al, 2018).…”
Section: Emissive Properties and Applicationssupporting
confidence: 81%
“…However, there is a frequency doubling effect of frequency distortion in the thermoacoustic effect, which means that the frequency of the generated sound is twice that of the input AC (alternating current). In the field of thermoacoustics, most research tends to focus on the improvement of sound pressure levels and electroacoustic conversion efficiency, but ignore the frequency doubling effect of thermoacoustic speakers [16][17][18][19][20][21]. Barnard et al only briefly summarized the advantages and disadvantages of one method (superimposing the DC bias on the AC excitation) to suppress the frequency doubling effect.…”
Section: Introductionmentioning
confidence: 99%
“…With an increasing number of graphene sheets, the HCPUA of the material increases, resulting in poorer electrothermoacoustic performance [35]. This was also supported by Xing et al [15]. In addition, Xing et al demonstrated that high substrate thermal effusivity, low thermal conductivity of the surrounding medium and high HCPUA of the thermoacoustic material reduces thermal dissipation, resulting in poorer electro-thermoacoustic performance (Figure 13 and Figure 14) [15].…”
Section: Graphenementioning
confidence: 82%
“…Generally, a good material used for thermoacoustic sound generation needs to have a high thermal conductivity (κ) and low specific heat capacity (Cp). High thermal conductivity is required for efficient dissipation of the induced thermal energy into its surrounding medium, while a low specific heat capacity is needed to decrease the amount of thermal energy required to increase the material temperature [14,15]. Low thickness is also desired to minimize the heat capacitance per unit area (HCPUA) of the material [14,15].…”
Section: List Of Tablesmentioning
confidence: 99%
See 1 more Smart Citation